1795 : [large type] the Order of the Furies - Natt och Dag, Niklas, 1979- ([Cardell & Winge], 2025)
"For more than a year, Emil Winge has dedicated himself to capturing the diabolical Tycho Ceton, with the invaluable assistance of one-armed army veteran and watchman Jean Michael Cardell. Their mission is made more difficult by the ever-increasing paranoia gripping Sweden's royal family, who fear that a bloody revolution is brewing. A letter with the names of the revolutionary conspirators is said to be in the possession of Anna Stina Knapp, a good friend to Cardell. Now, Anna is missing and Cardell is determined to find her before the secret police take her into custody. While Winge and Cardell fight for justice, they find themselves caught between powerful enemies those who will do anything to maintain the status quo, and those who will only be satisfied with its total destruction."--